2013
DOI: 10.1007/s10029-013-1099-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of contralateral inguinal hernias in children: a prospective study of 357 unilateral inguinal hernias

Abstract: PurposePreviously, we established a pre-operative risk scoring system to predict contralateral inguinal hernia in children with unilateral inguinal hernias. The current study aimed to verify the usefulness of our pre-operative scoring system.MethodsThis was a prospective study of patients undergoing unilateral inguinal hernia repair from 2006 to 2009 at a single institution. Gender, age at initial operation, birth weight, initial operation side, and the pre-operative risk score were recorded. We analyzed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…3). Hoshino et al [10] study confirms that babies operated for left-sided inguinal hernia repair had a 5.5-fold incidence of metachrnous hernia but surprisingly in our study we did not find its correlation [10]. We encountered only 2 (2.24%) cases of metachronous hernias in GI, and none in GII.…”
Section: Discussionsupporting
confidence: 48%
“…3). Hoshino et al [10] study confirms that babies operated for left-sided inguinal hernia repair had a 5.5-fold incidence of metachrnous hernia but surprisingly in our study we did not find its correlation [10]. We encountered only 2 (2.24%) cases of metachronous hernias in GI, and none in GII.…”
Section: Discussionsupporting
confidence: 48%
“…The loss to follow-up can also be a problem in retrospective research that relies on reported follow-up methods such as clinical investigation, phone call, letter, or e-mail [ 13 , 14 ]. In contrast to previous studies, our cohort used NHIRD, which records almost all medical practices in Taiwan and is a national resource provided by the National Health Research Institutes of Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date, reports on adults have seldom discussed the risk factors for CIH repair. Unlike infants and children, the risk factors associated with and results of CIH repair have been widely discussed [ 4 , 5 ]. Only one study used a non-Medicare claims database to analyze the risk factors for treatment of CIH and showed that an older age and prostate disease were risk factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%